Analysis of Sharia Policy and Remuneration on Professionalism Through Human Resources - Amiur Nuruddin; Saparuddin Siregar; Dahrani Dahrani (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Islamic banking as a business institution based on sharia values ​​and principles, the qualifications and quality of human resources clearly demands an integration between